Comparison of reversible traction substation power supply solutions for urban rail transit - SUN Jianjun; CHEN Sunan; MENG Meng; DENG Haotian; YIN Kun (机车电传动, 2025)
To pursuit low-carbon economy objectives amid the rapid development of rail transport, this study focuses on comparing traction substation power supply solutions for urban rail transit. The aim is to explore optimal strategies for achieving comprehensive energy conservation in rail transit systems. The research emphasized the efficient utilization of regenerative braking energy and its effect on overall system energy consumption. A comparative analysis was conducted between traditional rectifier power supply solutions and alternatives incorporating regenerative braking energy utilization equipment, to highlight differences in traction energy consumption. In a subsequent case study based on Qingdao metro line 9, simulations were conducted to analyze overall energy consumption performance under various power supply solutions. The results revealed that, under high-density train operation conditions, the energy storage-feedback integrated supply demonstrated a 13.76% reduction in daily traction energy consumption, which significantly decreased the traction energy consumption of the power supply system. Meanwhile, the fully reversible converter supply combined with an energy dispatching management system achieved a reduction of up to 14.65% in daily traction energy consumption across different train departure intervals.